Analisis Kinerja Jalan Abunawas Kota Kendari Akibat Penerapan Sistem Lalu Lintas Satu Arah - Irwan Lakawa; Vickky Anggara Ilham; Anastsya Fahira (Sultra Civil Engineering Journal (SCiEJ), 2026)
This study discusses the traffic characteristics and performance of Abunawas Street, Kendari City before and after the implementation of the one-way traffic flow system (SSA). The analysis was conducted on two road segments by considering traffic volume, average vehicle speed, and degree of saturation (DJ). The results showed that the highest traffic volume was recorded on Monday in Segment 1 at 742.6 smp/hour and Segment 2 at 385.8 smp/hour at 16.00–17.00 WITA. On Saturday, the highest volume in Segment 1 reached 855.2 smp/hour at 17.00–18.00 WITA, while in Segment 2 it was 389.7 smp/hour at 16.00–17.00 WITA. The average speed of light vehicles (MP) also showed variations, with the highest speed on Monday in Segment 1 at 26.2 km/hour and Segment 2 at 24.6 km/hour. On Saturday, the highest speed recorded was 25.4 km/h in Segment 1 and 25.2 km/h in Segment 2. In terms of road performance, the highest DJ value before the implementation of SSA was 0.50. After the implementation of SSA, the DJ decreased to 0.19. These results indicate that the implementation of SSA has an impact on road performance, despite a decrease in the DJ value